HPV73 a nonvaccine type causes cervical cancer. Issue 3 (29th April 2019) - Amaro‐Filho, Sergio M.; Gradissimo, Ana; Usyk, Mykhaylo; Moreira, Fabio C.B.; de Almeida, Liz M.; Moreira, Miguel A.M.; Burk, Robert D.
Abstract : HPV73 is classified as possibly oncogenic. It is neither routinely evaluated in HPV screening, nor covered by any of the prophylactic vaccines. We sought to investigate the carcinogenic characteristics of HPV73. Molecular studies were performed on eight cervix cancer biopsy specimens containing HPV73 from a cross‐sectional cancer cohort of 590 women referred to the National Cancer Institute in Rio de Janeiro, Brazil. Transcriptional activity of HPV73 was evaluated by detection of spliced transcripts of E6/E6* and E1^E4 in cDNA created from RNA isolated from fresh tissue. Disruption of viral E1 and E2 genes in the tumor DNA was assessed by overlapping PCR amplification. Evaluation of viral integration was performed using a customized capture panel and next‐generation sequencing, and an in‐house bioinformatic pipeline. HPV73 E6/E6* transcripts were found in 7/7 specimens with available RNA, and three also had HPV73 E1^E4 transcripts. Disruption of E1 and E2 genes was observed in 4/8 specimens. Integration of HPV73 sequences into the cancer cell genomes was identified in all cervix cancer tissues. These results provide evidence that HPV73 is an oncogenic virus that can cause invasive cervix cancer. With current molecular screening and HPV vaccination, not all cervix cancers will be prevented. Abstract : What's new? Several HPV viruses classified as "possibly" oncogenic are not routinely evaluated in HPV screening; nor are they covered by current prophylactic vaccines. In this study, the authors examined one such virus, HPV73, which occurs with a serologic prevalence as high as 14% in some regions. They found that HPV73 can, indeed, cause cervical cancer. It is likely that, due to these low‐prevalence HPVs, current screening and vaccines will fail to eliminate a proportion of cervical cancers. Population specific prevention efforts may thus need to be reevaluated.